The impacts of the milk pricing policy in Zimbabwe - Rodríguez, G. (1987)
Analyses the effects of government price policies on the production and consumption of milk in Zimbabwe. Gives an overview of the Dairy Marketing Board which is responsible for the collection and distribution of commercial milk products at prices set by the government. Discusses the implications of changes in the milk producer price for the opportunity costs of land and animal draught power in the communal areas. Describes the trends in the consumption of dairy products and aggregate demand relationships for whole milk and milk products.